Tinjauan Hukum Pidana Islam Terhadap Sanksi Koruptor dalam Pasal 603 KUHP Baru - Izzi, Muhammad (UNIB Press, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) has brought significant changes to the formulation of sanctions for corruption perpetrators. The implementation of these sanctioning norms has become increasingly urgent to examine following the ratification of Law Number 20 of 2025 concerning the Criminal Procedure Code (National KUHAP), which takes effect simultaneously with Law No. 1 of 2023. The integration of these two regulations marks a total transformation within the Indonesian criminal justice system, necessitating an in-depth analysis of the national legal instrument's readiness to accommodate Islamic justice principles toward corruption offenses. One of the primary controversies is Article 603, which sets the minimum prison sentence at 2 years, lower than the previous regulation. This study aims to analyze the construction of sanctions in Article 603 of the new Criminal Code and review them through the perspective of Islamic Criminal Law (Jinayah). The research method employed is normative legal research with a statutory approach and a comparative approach. The results indicate that corruption in Islamic law is classified as jarimah ta’zir because it constitutes an act that destroys the social order (fasad fil ardh). Normatively, the sanctions in Article 603 of the Criminal Code remain within the realm of the ruler's authority (ulil amri) to determine the severity of the punishment. However, the Jinayah perspective emphasizes that the imposition of sanctions must fulfill the elements of zawajir (deterrent effect) and zawabir (atonement). The reduction of the minimum sanction in the new Criminal Code is feared to weaken the zawajir aspect, thus requiring judicial ijtihad in sentencing to remain oriented toward the public interest (mashlahah mursalah) and the protection of property (hifzh al-maal).